Penggunaan Metode Peta Konsep dalam Pembelajaran SKI Kelas VIII di MTs Buluspesantren Kabupaten Kebumen - Sulastri; Noor Aziz; Firdaus (QuranicEdu: Journal of Islamic Education, 2023)
This research aimed to determine the application of the concept map method, the impact of the concept map method, as well as the obstacles that existed in implementing the concept map method for class VIII at MTs Bulus Pesantren Kebumen. This research used descriptive qualitative research. This research used data collection techniques with interview, observation, and documentation methods. The results of the research showed that there were many ways to apply the concept map method at MTs Buluspesantren. The application of the concept map method in SKI learning made students' enthusiasm in the learning process increase. It could be seen from the activeness of students in participating in the learning process. The obstacles that existed in using the concept map method could be overcome by teachers adapting and understanding the characters of their students, so that the learning process could take place better.